2018
DOI: 10.17265/2328-2150/2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Chitosan Based Nanocomposite Synthesized by Radiation: In Vitro Liver and Breast Cancer Cell Line

Abstract: A silver nanoparticle (AgNP) is likely to provide an attractive object for combining a variety of biochemical properties with great therapeutic potential by using radiation. The present study explores the IC 50 value of chitosan-poly (vinyl alcohol) hydrogel (Cs/PVA) and Ag-doped chitosan-poly (vinyl alcohol) (Cs/PVA/Ag) nanocomposite in view of their anticancer application. The aim was to develop (Cs/PVA) based hydrogel synthesized by gamma radiation which could behave both as a nanoreactor for Ag nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Bhatnagar et al 68 showed that SNPs fabricated using extracellular pigment from Talaromyces purpurogenus have a significant cytotoxicity effect against liver cancer cell line. Abaza et al 69 showed that Cs/PVA/Ag nanocomposites caused in killing 50% of HepG2 cells at 43.7 µg/mL. Based on these data, D-SNPs may be a potent antitumor agent against HepG2 with low IC 50 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Bhatnagar et al 68 showed that SNPs fabricated using extracellular pigment from Talaromyces purpurogenus have a significant cytotoxicity effect against liver cancer cell line. Abaza et al 69 showed that Cs/PVA/Ag nanocomposites caused in killing 50% of HepG2 cells at 43.7 µg/mL. Based on these data, D-SNPs may be a potent antitumor agent against HepG2 with low IC 50 .…”
Section: Resultsmentioning
confidence: 97%
“…Martins et al 72 showed that a polyelectrolyte complex containing SNPs exerted cytotoxic effects against Caco-2 cells, but not healthy African green monkey cells (VERO cells), at concentrations above 100 µg/mL. Comparing the chemically synthesized SNPs, 69,72 D-SNPs showed a potent anticancer activity with low IC 50 values and may be an alternative material to treat cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The estimated half maximal inhibitory concentration (IC50) value was found to be 31.2 μg/mL. Abaza et al [22] in 2018 reported the percentage of inhibiting fraction of Cs/PVA/AgNP in MCF7 cell line at 100 ug/mL was 61.8% and 80% with IC50 value of 60 and 52.5 μg/mL in (1:9) and (4:6) concentration respectively. The expected mechanism of AgNP induced toxicity being in the interactions between nanomaterials and cells [42].…”
Section: Resultsmentioning
confidence: 98%
“…Patil and his colleague [1] also, observed 50% of cell inhibition at AuNPs concentration of approximately 150 μg/mL and the 200 μg/mL sample reduced all cells to around 20% viability. On the other hand, Abaza et al [22] in 2018 reported that the silver-doped chitosan-poly (vinyl alcohol) (Cs/PVA/AgNP) inhibition fraction of HepG2 cell proliferation at 50 ug/mL in concentration of (4:6) and (1:9) was 54.4% and 40.8 respectively. The IC 50 value of concentration (4:6) was 43.7 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation